"That's Not the Only Reason I'm Watching the Game": Women's (Hetero)Sexual Desire and Sports Fandom. (December 2018) - Esmonde, Katelyn; Cooky, Cheryl; Andrews, David L.
Women make up increasingly large proportions of fan bases of the most popular spectator sports in the United States and are recognized as a viable marketing segment. Despite their growing cultural and economic presence, scholars have noted the stereotypical assumptions women sports fans routinely experience, particularly with regard to the widely held assumption that women's interest in men's sport is primarily motivated by heterosexual attraction to male athletes. Recently, feminist scholars have begun to investigate the role of heterosexual desire in shaping the experiences of women sports fans. Building on this literature, we examine the role of heterosexuality in women's fandom of men's sports, bringing to our research the feminist articulations of contradiction and a both/and ethos. In doing so, we empirically interrogate popular understandings of the role that women's heterosexual sexual desire plays in the consumption of men's sports through an examination of the lived experiences of women fans. Drawing on qualitative semistructured interviews with 11 self-identified women sports fans, we found that the participants navigated the marginalization of women's heterosexuality in sport fandom in four ways: by positioning the sexualization of athletes as antithetical to fandom, by challenging the exclusion of women's heterosexuality in the fan cultures surrounding men's sports, by discussing their own experiences of sexualizing athletes with guilt or ambivalence, and by downplaying the role that sexual attraction plays in their own fandom. We conclude that the marginalization of women sports fans' heterosexual desire within the institutional center of sports denies important facets of their experience and thereby upholds normative understandings of gendered sexuality that underpin masculine hegemony in sport.